Contemporary theories of religion: a critical companion - Stausberg, Michael (Routledge, 2009)
Interest in theories of religion has never been greater. Scholars debate single theoretical approaches in different scholarly journals, while the 'new atheists' such as Richard Dawkins and Daniel Dennett criticize the whole idea of religion. For everyone eager to understand the current state of the field, Contemporary Theories of Religion surveys the neglected landscape in its totality. Michael Stausberg brings together leading scholars of the field to review and discuss seventeen contemporary theories of religion. As well as scholars of religion, it features anthropologists, archaeologis